2006
DOI: 10.1074/jbc.c500457200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fibroblast Growth Factor-23 Signaling by Klotho

Abstract: The Klotho gene encodes a 130-kDa single-pass transmembrane protein with a short cytoplasmic domain (10 amino acids) and is expressed predominantly in the kidney. Mice carrying a loss-of-function mutation in the Klotho gene develop a syndrome resembling human aging, including shortened life span, skin atrophy, muscle atrophy, osteoporosis, arteriosclerosis, and pulmonary emphysema (1). Conversely, overexpression of the Klotho gene extends the life span and increases resistance to oxidative stress in mice (2-4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
1,105
3
37

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,215 publications
(1,174 citation statements)
references
References 27 publications
16
1,105
3
37
Order By: Relevance
“…The wide-ranging activity of klotho raises the possibility that regulation of Ca and phosphate metabolism is an Urinary P ↑ Urinary Ca ↓ essential feature of many systems of the body, not just those connected with the skeleton. Further information on this area of discussion is available (1,20,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) .…”
Section: Low Serum Calciummentioning
confidence: 99%
“…The wide-ranging activity of klotho raises the possibility that regulation of Ca and phosphate metabolism is an Urinary P ↑ Urinary Ca ↓ essential feature of many systems of the body, not just those connected with the skeleton. Further information on this area of discussion is available (1,20,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) .…”
Section: Low Serum Calciummentioning
confidence: 99%
“…These mutations replace the arginine (R) residues at positions 176 or 179 with glutamine (Q) or tryptophan (W) within a 176 RXXR 179 / S 180 subtilisin-like proprotein convertase (SPC) site that separates the conserved FGF-like N-terminal domain from the variable Cterminal tail (2)(3)(4). Acting through the coreceptor α-Klotho (5) and a fibroblast growth factor receptor (FGFR) (5,6), FGF23 reduces renal phosphate reabsorption through down-regulation of the sodium phosphate cotransporters NPT2a and NPT2c and suppresses kidney 1,25(OH) 2 vitamin D production by inhibiting and increasing vitamin D 1α-hydroxylase (Cyp27b1) and 24-hydroxylase expression (Cyp24), respectively (7). Compared with WT Fgf23 protein, ADHR-mutant FGF23 shows increased but not complete resistance to SPC proteolytic cleavage (3,4).…”
mentioning
confidence: 99%
“…FGF23 contains a consensus binding domain for FGFRs and several studies have suggested that FGF23 may bind and activate signaling through one or more FGFRs [31][32][33]. Recent in vivo genetic manipulation studies suggest that both FGF23 and KLOTHO act through a common signaling pathway [30] and that KLOTHO facilitates FGF23 binding to an FGFR [34]. Of relevance is the absence of the canonical FGFR binding domain on the bioactive FGF23 180-251 fragment.…”
Section: Discussionmentioning
confidence: 99%